Suze Orman's 2009 action plan keeping your money safe & sound - Orman, Suze; Zitt, Dan; Sherratt, Scott; Random House Audio (New York : Random House Audio, 2008)
Internationally praised financial advisor and television host Suze Orman discusses just how her audience can readily begin the New Year. Here, Orman delves into such matters as credit, real estate, retirement, and overall spending
Title from container
Read by the author
Keywords: Finance, Personal